(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2018)
Present investigation assesses 25 Lamiaceous taxa as possibly Extinct (EX) from the flora of Bangladesh due to various anthropogenic activities. The study based on long term field investigation, examination of preserved herbarium specimens at different national and international herbaria and consultation of relevant floristic literature. These taxa have been previously reported from the area of Bangladesh about 70 to 200 years ago. Since then there have been no subsequent reports of occurrence and no collected specimens are available at any herbaria. Furthermore, this species could not be relocated from elsewhere in Bangladesh. Among these 25 taxa, Leucas mollissima Wall. ex Benth. (=L. decemdentata (Willd.) Sm.) and Elsholtzia incisa Benth. (=E. stachyodes (Link.) Raizada and Saxena) have been reported from the area about 193 and 77 years ago respectively. 18 species (72%) have been reported from Sylhet; of which, 13 species, viz. Aphanochilus blandus Benth. (=Elsholtzia blanda (Benth.) Benth.), Gomphostemma lucidum Wall. ex Benth., G. melissifolium (Roxb.) Wall. ex Benth., Plectranthus hispidus Benth. (=Isodon hispidus (Benth.) Murata), Plectranthus gerardianus Benth. (=Isodon lophanthoides (Buch.-Ham. ex D. Don) Hara), Leucas vestita Benth., Orthosiphon incurvus Benth., Phlomis rugosa Benth. (=Paraphlomis javanica (Blume) Prain), Geniosporum strobiliferum Wall. ex Benth. (=Platostoma coloratum (D. Don) A.J. Paton), Geniosporum parviflorum Benth. (=Platostoma palustre (Blume) A. J. Paton), Pogostemon parviflorus Benth., Dysophylla strigosa Benth. (=Pogostemon strigosus (Benth.) Benth.), and Scutellaria discolor Wall. ex Benth. were named based on type specimens collected from area by Wallich‟s collectors, and Microtoenia griffithii Prain was named based on Griffith‟s collection from East Bengal (current Bangladesh) Sinne loco. Enumeration of these possibly extinct taxa is prepared with data on habit, habitat, phenology, global distribution, recorded localities, specimens examined, and notes with some photographs of type/herbarium specimens. J. Biodivers. Conserv. Bioresour. Manag. 2017, 3(2): 19-34